Conversations About Poverty in New Zealand: How the News Media Framed Metiria Turei’s Confession and Resignation Prior to the 2017 General Election - Johnson, Karen (Auckland University of Technology, 2020)
This thesis analyses how the news media framed Metiria Turei’s confession and resignation prior to the 2017 General Election. In particular it investigates how poverty is portrayed, in the 10 weeks of the campaign period leading up to the election, by analysing 18 stories from four New Zealand news media outlets: New Zealand Herald, Stuff, Radio New Zealand and Newsroom. Each of these stories depicts or refers to poverty in some way. The media claims to play a watchdog role in society by disseminating transparent and unbiased news (Lange & Ward, 2004). The study discusses whether or not these four news media outlets meet this objective. Poverty is a complex social and political issue, and the various frames in media discourse provide a map for understanding it. How citizens think about poverty is shown to be dependent on how the issue is framed by the news media (Iyengar, 1990). This research starts with how mainstream and independent news media covered Turei's speech at the Green Party conference on July 16, 2017, continues through to her resignation as the co-leader of the party on August 9, 2017 and concludes on September 24, 2017, the day after the election results were announced. The research seeks to investigate how the news media framed poverty in reporting Turei’s speech and subsequent resignation as Green Party co-leader. The methodology is qualitative. Discourse analysis is the method that examines the data set using four tools: theory of agenda setting, theory of framing, analysis of themes, and theory of attribution. Van Leeuwen (2008) observes that discourses not only represent what is going on, they also evaluate it, ascribe purpose to it, justify it, and, as is shown in this analysis, the representations of poverty have become far more socially and politically influential than the social practice itself. This research shows how news media introduced and discussed the issue of poverty in the election period. The study found seven distinct themes used as framing devices in poverty reporting; attributions, adjectives, metaphors, analogies, euphemisms, dysphemisms, and the significance of what isn’t mentioned. This analysis showed that the news media presented poverty in a way that influenced public perception of the confession and resignation of Turei, and perceptions of poverty in the build up to the election. Ten dominant thematic headings emerged. These were fraud, criminality and deceit, political process, positive impact, political naivety, internal democracy, undermining the left, promoting the left, poverty, gender, and martyrdom. The changes in discourse at various stages shift from a nuanced to a polarised message, labelling Turei’s historic behaviour as fraud, and then from a polarised to a nuanced message opening an increasingly meaningful conversation about poverty. The thesis identifies major problems with news media reporting about poverty in reference to Turei’s resignation, such as the lack of an agreed definition of poverty in New Zealand. Another critical point is connected to the political power of the news media in election times. News media have an important role in reporting poverty responsibly. They have the power to shape opinions that lead to voting decisions and therefore to social policy making in New Zealand.
Keywords: News media; Perception; Welfare; Poor; Homeless; General election; Journalism